Using Hebbian-Type Stimulation to Rescue Arm Function After Stroke: Study Protocol for a Randomized Clinical Trial - Xu, Rong; Zhu, Guang-Yue; Zhu, Jun; Wang, Yong; Xing, Xiang-Xin; Chen, Lin-Yu; Li, Jie; Shen, Fu-Qiang; Chen, Jian-Bing; Hua, Xu-Yun; Xu, Dong-Sheng (Frontiers in Neural Circuits, 2022)
Background Upper-extremity hemiplegia after stroke remains a significant clinical problem. The supplementary motor area (SMA) is vital to the motor recovery outcomes of chronic stroke patients. Therefore, rebuilding the descending motor tract from the SMA to the paralyzed limb is a potential approach to restoring arm motor function after stroke. Paired associative stimulation (PAS), which is based on Hebbian theory, is a potential method for reconstructing the connections in the impaired motor neural circuits. The study described in this protocol aims to assess the effects of cortico–peripheral Hebbian-type stimulation (HTS), involving PAS, for neural circuit reconstruction to rescue the paralyzed arm after stroke. Methods The study is a 4-month double-blind randomized sham-controlled clinical trial. We will recruit 90 post-stroke individuals with mild to moderate upper limb paralysis. Based on a 1:1 ratio, the participants will be randomly assigned to the HTS and sham groups. Each participant will undergo 5-week HTS or sham stimulation. Assessments will be conducted at baseline, immediately after the 5-week treatment, and at a 3-month follow-up. The primary outcome will be the Wolf Motor Function Test (WMFT). The secondary outcomes will be Fugl-Meyer Assessment for Upper Extremity (FMA-UE), Functional Independence Measure (FIM), and functional near-infrared spectroscopy (fNIRS) parameters. The adverse events will be recorded throughout the study. Discussion Upper-limb paralysis in stroke patients is due to neural circuit disruption, so the reconstruction of effective motor circuits is a promising treatment approach. Based on its anatomical structure and function, the SMA is thought to compensate for motor dysfunction after focal brain injury at the cortical level. Our well-designed randomized controlled trial will allow us to analyze the clinical efficacy of this novel Hebbian theory-based neuromodulation strategy regarding promoting the connection between the cortex and peripheral limb. The results may have significance for the development and implementation of effective neurorehabilitation treatments. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [ChiCTR2000039949].